Teacher repetition as an instructional resource for classroom interaction: Three pedagogical actions in kindergartens in an EFL context. (June 2018) - Roh, Teri Rose Dominica; Lee, Yo-An
Abstract: Teacher repetition in SLA has been considered to be a vital language input that assists language comprehension and acquisition and therefore, their linguistic or functional patterns have been of analytic interest. Teacher repetition is, however, also important for its pedagogical role in leading nonnative students through English lessons. In this study, the analytic emphasis is placed on specifying teaching actions associated with repeated language use and its effect on L2 classroom interaction. Following conversation analysis (CA), the present study examined English lessons in two Korean kindergartens in which a native teacher of English interacted with nonnative children with minimum English proficiency. The sequential analyses of the class sessions identified three distinctive pedagogical actions arising from teacher repetition: eliciting synchronized English responses from the student cohort; having students recognize and practice a target language item; and pursuing particular answers. These findings provide procedural accounts of practical routines through which language teachers organize children's participation and guide them through the English lessons. From the descriptions presented in this study, researchers and practitioners can make informed judgments about what pedagogical actions are performed and what challenges are faced in teacher repetition for young learners of English. Highlights: Tracing sequential organization of classroom discussion allow us to specify the work-practices engaged by teaching professionals during their daily classroom routines. Linguistic patterns found in repetition alone do not describe a litany of practical and contingent work of understanding by classroom teachers and their students. There is a need to trace the varied functions of repetition enacted in common tasks in kindergarten classrooms, such as establishing participatory norms, pursing questions and engaging in language practices. Repetition is something that classroom teachers routinely use to organize students into a cohort, to move from presentation to practice and to purse a response.